The Effect of Work Engagement and Self-Efficacy on Job Burnout of Credit Analyst - Ni Nyoman Sri Rahayu Damayanti (AIBPM Publisher, 2019)
The purpose of this research is to determine the effect of work engagement and self-efficacy on credit analyst’s job burnout. The research takes place at Bank Rakyat Indonesia Renon Branch Office. Banking is one of an important sector that related to public welfare. Credit is one of bank’s product that has several types. Credit analyst has to evaluating the data and does other supporting aspects that submitted by the credit applicant in order to making a decision whether the credit application is accepted or rejected. If the credit application does not properly analyzed, it will increase an inability of debtor to repay the credit installment. Job burnout is one aspect that influence negligence in analyze a credit application. Job burnout is a condition with emotional fatigue, physical fatigue, and lack of energy which can cause a person's low performance. BRI is the largest profit bank in Indonesian banking industry and always grows up to 2017. High number of debtors and credit applications can also increase the workload and job burnout for the analyst. Job burnout can be minimized by a high work engagement between worker and their job. Work engagement is a condition when worker easier to manage work relationship and manage stress on work pressure. This condition is needed for increasing worker’s motivation. High work engagement will prevent job burnout. Self-efficacy also will prevent job burnout. Person with high self-efficacy has a good competence to face challenges in their workplace. Ability to perform difficult task will contribute positively to prevent job burnout. This study used primary data source collected by questionnaire technique. Respondents in this study were credit analysts at Bank Rakyat Indonesia Renon Branch Office. Hypothesis was tested by using multiple linear regression analysis. The result showed that work engagement and self-efficacy had a negative and significant effect on job burnout of credit analyst. Further research can use more bank branch office to make a better generalization. The results of this study can be used as a consideration for Bank Rakyat Indonesia regarding aspects that can influence job burnout on their workers.